The Sublime, Ugliness and Contemporary Art: A Kantian Perspective - Kuplen, Mojca (Con-Textos Kantianos. International Journal of Philosophy, 2015)
The aim of this paper is twofold. First, to explain the distinction between Kant’s notions of the sublime and ugliness, and to answer an important question that has been left unnoticed in contemporary studies, namely why it is the case that even though both sublime and ugliness are contrapurposive for the power of judgment, occasioning the feeling of displeasure, yet that after all we should feel pleasure in the former, while not in the latter. Second, to apply my interpretation of the sublime and ugliness to contemporary art, and to resolve certain issues that have been raised in accounting for the possibility of artistic sublimity. I argue that an experience of a genuine artistic sublimity is an uncommon occurrence. I propose that the value of contemporary art can be best explained by referring to Kant’s notion of ugliness and his theory of aesthetic ideas.